COMPARATIVE STUDY REGARDING THE RISK PERCEPTION OF TSUNAMIS FROM EFORIE NORD (ROMANIA) AND NICE (FRANCE) COMMUNITIES - CONSTANTIN, Angela Petruţa; MOLDOVAN, Iren-Adelina; PARTHENIU, Raluca; LAVIGNE, Franck; GRANCHER, Delphine; IONESCU, Constantin (Studia Universitatis Babeș-Bolyai Ambientum, 2018)
The goal of this paper is to present a comparative study of the people perception from two different sites from Romania and France, regarding the tsunami risk in the Black and Mediterranean Seas communities. These two surveys over residents’ and tourists’ perception and preparedness of tsunami hazard were carried out for both towns, Eforie Nord(Romania) and Nice (France), in the frame of the ASTARTE project – „Assessment, Strategy And Risk reduction for Tsunamis in Europe” (EC Programme FP7).Data were collected by tsunami questionnaire developed in the project and translated in Romanian and French languages, and the questions are referring to: interviewee's relation to Eforie Nord and Nice sites, information about interviewed people, tsunami hazard knowledge/risk perception, evacuation issue, awareness of the existing warning system, information, and communication. A total of 256 subjects participated at surveys from both sites situated along coasts of Black and Mediterranean seas. The results of the survey showed a moderate level of tsunami preparedness and perception of people living in, working in, or visiting Eforie Nord and Nice sites, our respondents mentioned the tsunami as third rank in both sites, coming after earthquakes and storms/pollution. Whatever the respondent's status (i.e. local population, or tourists), earthquakes and sea withdrawal are cited as tsunami warning signs by 62% and 60% of the respondents from Eforie Nord and by 30% and 31% of the respondents from Nice, respectively. When considering a future tsunami being generated in Eforie Nord, 36,3% of the respondents think that the place could be affected by a tsunami and the waves could reach more than 2-5 meters (heights cited by approx. 14% of respondents) or even more than 5-10 meters (values cited by 15% of interviewed people). Regarding the Nice site, 78% of the respondents think that the place could be affected by a tsunami in the future. With such a negative perception of tsunamis, it is not surprising that more than 29% of the respondents from Nice site expect waves of more than 10 m high. This study provided evidence that tsunamis recently occurred in the world have a significant impact on people’s preparedness and perception.